Pengaruh Implusive Buying dan Kualitas Produk terhadap Kepuasan Konsumen Generasi Z pada Platfrom Shopee di Kota Jambi - Bunga Praditya Ningsih; Husni Hasbullah; Garry Yuesa Rosyid (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the influence of impulsive buying and product quality on consumer satisfaction of generation Z on the Shopee platform in Jambi City. This study is motivated by the phenomenon of Shopee e-commerce which is a favorite in Indonesia, especially among generation Z who have consumptive characteristics and like unique shopping experiences. Data were collected from 96 generation Z respondents using a questionnaire. The results showed that the average respondent's assessment of impulsive buying was 347.87, and for product quality was 376.25. Multiple linear regression tests showed that there was a significant influence between impulsive buying and product quality on consumer satisfaction with an R square value of 0.522, which means that 52.2% of the variation in consumer satisfaction is explained by these two variables. This study is expected to contribute to the development of more effective marketing strategies for e-commerce business actors, especially those targeting the generation Z segment, by understanding the factors that influence impulsive buying decisions and consumer satisfaction levels.